Intrahousehold resource allocation: an overview - Haddad, Lawrence James; Hoddinott, John F.; Alderman, Harold (World Bank, 1994)
The authors examine the many complex factors that influence decisions made by households about how they spend time, money, and other resources. It shows that a more complete understanding of intrahousehold behavior can increase the likelihood that policies will reach the people they are intended to affect leading to better policies in areas such as food production, consumption, nutrition, and natural resource management.